"I Don't Want to See Myself as a Disabled Person": Continuous Positive Airway Pressure Devices and the Emergence of (Dis)ability as Subjectivity. (March 2018) - Zarhin, Dana
This article explains how the most recommended treatment for obstructive sleep apnea (OSA), the continuous positive airway pressure (CPAP) device, acts and interacts with users' bodies, sleep partners' bodies, and cultural discourses to produce emotions and practices that generate the subjectivity of a disabled or abled person. Drawing upon in-depth interviews with OSA patients, this article illustrates how introducing CPAP devices into patients' lives may disturb their sleep and breathing, diminish their independence, disfigure their appearance, and problematize intimacy with bed partners, thereby disrupting both the fleshy body and the culturally preferred image of a healthy, independent, and attractive individual. In response, many patients reject this treatment. (Dis)ability as a subjective state is shown to emerge from associations in a network composed of heterogeneous entities that have agency. That is, disabled subjectivity emerges when the device prevents individuals from accomplishing what they consider to be the essential and socially significant aspects of sleep and primarily its disembodied and interembodied aspects.